Reintroduction of Groenlandia densa (L.) Fourr. – experiences and suggestions - Wróbel, Mariola; Furdyna, Artur; Miller, Tymoteusz (Biodiversity: Research and Conservation, 2020)
Groenlandia densa (L.) Fourr. is a native species in Poland of evergreen hydromacrophyte occurring in water-sources or groundwater-fed watercourses. It is a critically endangered taxon which requires active protection. To increase the chance of preserving G. densa population in Western Pomerania, this plant was introduced to the Grabowa and Radew river systems in the Natura 2000 areas PLH 320022 “Radew, Chociela and Chotla Valley” and PLH 320003 “Grabowa Valley”, on a total of 33 sites. In the Radew and its tributaries (Chociel, Zgniła Struga), 6 out of 20 sites were maintained, where reintroduction was successful, while in the Grabowa and its tributaries (Błotnica, Biegała), only 3 out of 13 reintroduction sites survived, and reintroduction in the remaining ones did not bring expected results. Favorable conditions for G. densa were found in initial stages of Beruletum submersae Roll 1938 plant community.